Vascular endothelial injury exacerbates coronavirus disease 2019: The role of endothelial glycocalyx protection. (30th August 2020) - Okada, Hideshi; Yoshida, Shozo; Hara, Akira; Ogura, Shinji; Tomita, Hiroyuki
Abstract: The potential for a rapid increase in severity is among the most frightening aspects of severe acute respiratory syndrome coronavirus 2 infection. Evidence increasingly suggests that the symptoms of coronavirus disease‐2019 (COVID‐19)‐related acute respiratory distress syndrome (ARDS) differ from those of classic ARDS. Recently, the severity of COVID‐19 has been attributed to a systemic, thrombotic, and inflammatory disease that damages not only the lungs but also multiple organs, including the heart, brain, toes, and liver. This systemic form of COVID‐19 may be due to inflammation and vascular endothelial cell injury. The vascular endothelial glycocalyx comprises glycoproteins and plays an important role in systemic capillary homeostasis maintenance. The glycocalyx covers the entire vascular endothelium, and its thickness varies among organs. The endothelial glycocalyx is very thin in the pulmonary capillaries, where it is affected by gaseous exchange with the alveoli and the low intravascular pressure in the pulmonary circulation. Despite the clearly important roles of the glycocalyx in vascular endothelial injury, thrombosis, vasculitis, and inflammation, the link between this structure and vascular endothelial cell dysfunction in COVID‐19 remains unclear. In this prospective review, we summarize the importance of the glycocalyx and its potential as a therapeutic target in cases of systemic COVID‐19.